Debate on Mission, Issues from the Indian Context - Karokaran, Anto (Journal of Dharma, 1981)
H.E. Hoefer (ed.) Debate on Mission, Issues from the Indian Context, xix A- 470. Gurukul Lutheran Theological College, Madras, India.